Educational Management Strategy in the Implementation of Recognition of Prior Learning (RPL) in the Modern Education Era - Lina Sukanti; Mohd Imraan (The International Journal of Education Management and Sociology, 2026)
This study aims to examine educational management strategies in the implementation of Recognition of Prior Learning (RPL) in the modern education era. RPL has emerged as an innovative approach that recognizes knowledge, skills, and competencies acquired through formal, non-formal, and informal learning experiences. In the context of rapid technological advancement and globalization, effective management strategies are essential to ensure that RPL programs are implemented efficiently, transparently, and in alignment with labor market demands. This research employs a qualitative approach with a descriptive-analytical design, utilizing data collected through literature review and document analysis. The findings indicate that successful RPL implementation depends on several key factors, including institutional commitment, clear regulatory frameworks, standardized assessment procedures, competent assessors, and the integration of digital technologies. Furthermore, effective management strategies contribute to improving access to education, enhancing student competence, and supporting lifelong learning. However, challenges such as limited awareness, lack of standardization, and administrative complexity continue to hinder optimal implementation. Therefore, strengthening governance, enhancing collaboration among stakeholders, and leveraging digital innovation are necessary to maximize the effectiveness of RPL programs in the modern education era.